Market sentiment assessment of investors on Bangladeshi Pharmaceutical Stocks incorporating multiples valuation approach - Mikath, Tazir Chowdhury (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.